CP-126 Review of novel oral anticoagulant prescribing for stroke prevention in atrial fibrillation in a teaching trust. (24th February 2014) - Robinson, G; Wright, P; Hamedi, N; Antoniou, S; Virdi, G; Duggan, S; Cooper, P
Abstract : Background: Following the introduction of novel oral anticoagulant agents (NOACs) dabigatran and rivaroxaban as an option for stroke prevention in atrial fibrillation (AF), local guidance has been developed to facilitate safe and effective prescribing of these agents. Purpose: The purpose of this audit was to review prescribing of NOACs against local guidance and identify trends in prescribing against the following standard: NOACs should be prescribed in accordance with the product license, with appropriate dosage reduction as a second line agent only, reserved for when warfarin unsuitable. Materials and methods: From March 2012 to February 2013, patients were identified and data was gathered from patient records and clinical notes. Results: 32 of the 33 patients started on NOACs had a stroke risk score (CHA2 DS2 -VASc) of ≥1 and all patients were started only when warfarin was inappropriate in accordance with the guidance. The reasons for prescribing are highlighted in Table 1 . All patients who required dose reductions received an appropriate dose. However of the 27 patients prescribed a reduced dose, 8 had no clear indication highlighted. Conclusions: The audit suggests initiation of NOACs is appropriate, with the majority prescribed according to local guidance and initiated due to labile INRs or inability to comply with the monitoring requirements of warfarin. Dosing of dabigatran was predominantly at the lower dose, most commonly due to age and impaired renal function. The unaccounted for dose reductions require further investigation, as using lower doses may have reduced effectiveness compared to warfarin, and as such, full therapeutic doses should be the preferred choice unless not tolerated. No conflict of interest.